Selective Control of Fear Expression by Optogenetic Manipulation of Infralimbic Cortex after Extinction - Kim, Hyung-Su (2016)
Evidence from rodent and human studies has identified the ventromedial prefrontal cortex, specifically the infralimbic cortex (IL), as a critical brain structure in the extinction of conditioned fear. However, how IL activity controls fear expression at the time of extinction memory retrieval is unclear and controversial. To address this issue, we used optogenetics to precisely manipulate the activity of genetically targeted cells and to examine the real-time contribution of IL activity to expression of auditory-conditioned fear extinction in mice. We found that inactivation of IL, but not prelimbic cortex, impaired extinction retrieval. Conversely, photostimulation of IL excitatory neurons robustly enhanced the inhibition of fear expression after extinction, but not before extinction. Moreover, this effect was specific to the conditioned stimulus (CS): IL activity had no effect on expression of fear in response to the conditioned context after auditory fear extinction. Thus, in contrast to the expectation from a generally held view, artificial activation of IL produced no significant effect on expression of non-extinguished conditioned fear. Therefore, our data provide compelling evidence that IL activity is critical for expression of fear extinction and establish a causal role for IL activity in controlling fear expression in a CS-specific manner after extinction.